The Academic Origins of Economics Faculty - Todd R. Jones; Arielle A. Sloan (Institute of Labor Economics (IZA), 2021)
We use roster data of 96 top U.S. economics departments to document the academic origins of their tenure-track faculty. Academic origins may have implications for how undergraduate (B.A.) and doctoral (Ph.D.) students are trained and placed, as well as the type of research produced. We find that faculty educated at top-ranked Ph.D. universities are overrepresented; e.g., over half of our sample attended a top 15 university, and over a third attended a top six university. We find similar, but less pronounced, patterns for B.A. origins; e.g., over a third of those with a U.S. B.A. attended a top 15 university.
Keywords: I2; I23; J2; J4; 330; doctoral origins; Ph.D. origins; bachelor origins; B.A. origins; academic labor market; economics faculty